Using neutron diffraction to examine the onset of mechanical twinning in calcite rocks. (July 2017) - Covey-Crump, S.J.; Schofield, P.F.; Oliver, E.C.
Abstract: Experimental calibration of the calcite twin piezometer is complicated by the difficulty of establishing the stresses at which the twins observed in the final deformation microstructures actually formed. In principle, this difficulty may be circumvented if the deformation experiments are performed in a polychromatic neutron beam-line because this allows the elastic strain (and hence stress) in differently oriented grains to be simultaneously monitored from diffraction patterns collected as the experiment is proceeding. To test this idea small strain (<0.3%), uniaxial compression experiments have been performed on Carrara marble (grain size 150 μm) and Solnhofen limestone (5 μm) at temperatures of 20°–600 °C using the ENGIN-X instrument at the ISIS neutron facility, UK. At the lowest temperatures (25 °C Carrara; 200 °C Solnhofen) the deformation response was purely elastic up to the greatest stresses applied (60 MPa Carrara; 175 MPa Solnhofen). The sign of the calcite elastic stiffness component c 14 is confirmed to be positive when the obverse setting of the calcite rhombohedral lattice in hexagonal axes is used. In the Carrara marble samples deformed at higher temperatures, elastic twinning was initiated at small stresses (<15 MPa) in grains oriented such that the Schmid factor for twinning was positive on more than one e -twin system. At greater stresses (65 MPa at 200 °C decreasing to 41 MPa at 500 °C) there was an abrupt onset of permanent twinning in grains with large Schmid factors for twinning on any one e -twin system. No twinning was observed in the Solnhofen limestone samples deformed at 200° or 400 °C at applied stresses of <180 MPa. These results highlight the potential of this approach for detecting the onset of twinning and provide, through experiments on samples with different microstructures, a strategy for systematically investigating the effects of microstructural variables on crystallographically-controlled inelastic processes. Graphical abstract: Highlights: Twinning in calcite rocks detected during deformation using neutron diffraction. Onset of elastic twinning in Carrara marble at ∼10 MPa. Onset of permanent twinning in Carrara marble at 64.5 MPa (200 °C). No twinning, elastic or permanent, in fine-grained Solnhofen limestone at <180 MPa. Calcite stiffness c 14 positive for obverse setting of unit cell in hexagonal axes.